Statistical Analysis of the Relationship between Oil Prices and Industry Index Prices - Akbulaev, Nurkhodzha; Rahimli, Etimad (International Journal of Energy Economics and Policy, 2020)
The article is devoted to the study of the relationship between the level of industry indices and the oil market. It is proved that there are positive and negative effects associated with an increase in sales and oil prices and world indices. It is very difficult to establish a clear relationship between the level of industry indices and the development of the oil market, but statistical methods help to identify existing relationships. The purpose of the article is to identify the relationship between oil price and industry index prices through statistical analysis. The objectives of the work are: to consider existing approaches to assessing the relationship between oil price and prices of industry indices through the review of literature, to consider theoretical aspects of the relationship between oil prices for indices of stock exchanges, to form a model of statistical analysis and to check it on specific data of the Moscow Stock Exchange. Statistical analysis of the relationship between oil prices and industry index prices has helped international organizations to develop preventive measures to support positive market effects and to boost global markets. Keywords: Correlation-regression analysis, industry indices, oil price, pair regression model, mean approximation error, interval prediction. JEL Classifications: C50, G10, G15 DOI: https://doi.org/10.32479/ijeep.8901